Characteristics of Liquid Product of Alkaline Treated Sargassum polycystum C.A. Agardh. from Lange Beach, Aceh - Anjar Purba Asmara; Endaruji Sedyadi; Ilma Fistannisa Zette (Marine Science Department Diponegoro University, 2020)
Sargassum is known to have potential ingredients, such as essential nutrients and minerals, which are important for agroindustry and the environment. This study aims to determine the proximate properties of Sargassum polycystum C.A. Agardh from Lange beach and the optimum extraction period arising the liquid product. The dried seaweed was extracted using 0.1% KOH at a constant temperature of 80°C for 120–600 mins. Furthermore, nutrients content, pH, electrical conductivity (EC) and total dissolved solids (TDS) of the afforded filtrate were quantified. As a result, the moisture, ash, fibre, carbohydrate, protein, and fat content were 7.16, 13.057, 20.33, 51.77, 6.12, and 1.57%, respectively. The value of pH, EC, and TDS ranged around 4.69–7.27, 0.013–0.078 dS.m-1, and 6.24–39.75 mg.L-1, respectively. The level of N, P, K, and organic C, were estimated around 0.30–0.81, 0.16–0.28, 0.15–0.20, and 0.32–0.80%, respectively. Meanwhile, the content of Na, Mg, Ca, Fe, Mn, and Zn were observed from 112.04–212.61, 24.60–33.57, 146.59–280.92, 416.22–630.69, 18.25–27.73, and 19.86–26.53 ppm, respectively. In conclusion, extraction for 120 mins seems to be preferable, as the observed parameters were above the minimum range.